2014
DOI: 10.1111/aji.12273
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Galectin‐3 Function in the Reproductive Tract by Identification of Binding Ligands in Human Seminal Plasma

Abstract: Problem Galectin-3 is a β-galactoside binding protein with immunomodulatory properties and exerts its extracellular functions via interactions with glycoconjugate ligands. Therefore, to elucidate the function of galectin-3, binding ligands in human seminal plasma were investigated. Method of Study Galectin-3 binding proteins were isolated from seminal plasma by affinity chromatography, and candidate ligands were identified by MS/MS. Biochemical methods were used to characterize the ability of galectin-3 to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 42 publications
0
16
0
1
Order By: Relevance
“…Yang et al [59] used a human cDNA phage display biopanning method to identify proteins interacting with CD13 and found that 70% of the isolated clones encoded galectin-3, which suggests that galectin-3 is a likely endogenous ligand of CD13. Furthermore, in a study that uses affinity chromatography to identify ligands of galectin-3 in seminal fluid, CD13 was found to be 1 of the 9 proteins identified [60]. Moreover, galectin-3 coimmunoprecipitates with CD13 in resting U-937 cells [61], and CD13 and galectin-3 colocalize in HUVECs after addition of exogenous galectin-3 [59].…”
Section: Discussionmentioning
confidence: 99%
“…Yang et al [59] used a human cDNA phage display biopanning method to identify proteins interacting with CD13 and found that 70% of the isolated clones encoded galectin-3, which suggests that galectin-3 is a likely endogenous ligand of CD13. Furthermore, in a study that uses affinity chromatography to identify ligands of galectin-3 in seminal fluid, CD13 was found to be 1 of the 9 proteins identified [60]. Moreover, galectin-3 coimmunoprecipitates with CD13 in resting U-937 cells [61], and CD13 and galectin-3 colocalize in HUVECs after addition of exogenous galectin-3 [59].…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-3-binding protein is a member of beta-galactoside binding lectins expressed in various cells and tissues 68 and this molecule has been previously found in epidydimal fluid of dairy bulls 48 . In humans, seminal galectin-3-binding protein plays multiple roles associated with semen liquefaction, sperm motility, angiogenesis in the female reproductive tract and as a pro-inflammatory agent 69 . In silico analysis detected an interaction between galectin-3 binding protein and clusterin, which is also over expressed in low fertility dairy bulls.…”
Section: Discussionmentioning
confidence: 99%
“…The population standard deviations were used as criteria to define bull fertility 74 and, for the present study, high and low fertility sires differed from the mean by at least 1.3 standard deviations. Factors that influence fertility performance of sires (breeding event, environmental factors and herd management) were adjusted to determine reliable fertility scores using threshold models 69 .…”
Section: Methodsmentioning
confidence: 99%
“…Gal-8 is the most abundant galectin in tumor cells of different origin [ 74 ], and is closely related to prostate carcinoma tumor antigen-1 (PCTA-1) [ 75 ]. Gal-3 is also reported to be a substrate for prostate-specific antigen (PSA) [ 101 ], and some of its glycoprotein ligands have been associated with prostasomes [ 102 , 103 , 104 ]. These findings suggest that Gal-8 and Gal-3 antagonists may be effective against reproductive and prostate cancer.…”
Section: Galectin Functionmentioning
confidence: 99%